The Effect Of Support Leader, Career Development And Compensation Of Motivation Nurse In Continuing Education Nursing In The Salewangang Regional Maros Public Hospital - Iswajidi -; Mattalatta - (STIE AMKOP, 2016)
ABSTRACT This study aims to identify and observe: (1). Influence of support led to nurses motivation. (2) the effect on the motivation of career development of nurses. (3) effect of compensation for nurses motivation. (4) how much influence the support of the leadership, career development and compensation to motivate nurses. (5) the variables that most influence between the support of the leadership, career development and compensation to motivate nurses. The method used in this research is survey method with quantitative approach, the study was conducted in hospitals Salewangang Maros with a population of 111, the sampling using the formula slovin by the number of sample was 87 respondents. Data were collected through questionnaires and direct observation. The research was carried out for 3 months. The results showed that: (1) there was an effect on motivation nurse-led support. (2) no effect on the motivation of career development of nurses. (3) no compensation effect on the motivation of nurses. (4) there are approximately 64.3% influence leadership support, career development and compensation to motivate nurses. (5) variable career development is the most dominant variable affecting motivation nurse. Keywords: support leadership, career development, compensation, motivation